Diagnostics and treatment of infectious esophagitis: clinical guidelines of the Russian gastroenterological association - V. T. Ivashkin; N. D. Yuschuk; I. V. Mayev; A. S. Trukhmanov; O. P. Alekseyeva; T. L. Lapina; S. S. Pirogov; A. V. Tkachev; A. A. Sheptulin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
.